Microbial dynamics of bioleaching consortia - Adeyemi, Adedolapo (Department of Chemical Engineering, 2025)
Owing to a decrease in the availability of mined ores as primary mineral sources and a push towards more environmentally sustainable production in the mining sector, there has been an increased interest in the use of historic tailings and electronic wastes for metal retrieval. Bioleaching is considered a suitable method for metal recovery from these wastes. This is because of its perceived low cost, environmental astuteness and its ability to nullify the potential environmental degradation that can occur as a result of these wastes accumulating. However, utilising these wastes is not without its challenges as lower-grade minerals often contain an abundance of metals and other compounds which could be toxic to bioleaching microorganisms and potentially impact performance. While studies on individual iron- and sulfur-oxidising species and their tolerance to metals have been reported for a subset of microbial species of interest, currently, minimal work has been done to quantify the negative effects of these metals when using mixed microbial communities. This information is important as mixed communities are used commercially. Understanding the dynamics and behaviours of the microorganisms within the bioleaching cultures has the potential to increase bioleaching performance and efficiencies as a better understanding would allow for better control of systems and their robustness. To better understand the impact these inhibitory metals may have on microorganisms, bioleaching tests were conducted. The aim of these tests was to determine the extent to which two chosen metals, nickel and chromium, affected the microbial consortia that were being used. Nickel and chromium were selected because they are metals found within e-wastes such as waste printed circuit boards (PCBs) that could potentially inhibit microorganisms at high enough concentrations. Two similar microbial communities were utilised (BRGM-KCC and BIOX® culture) consisting of different proportions of Leptospirillum ferriphilum, Acidithiobacillus caldus, Sulfobacillus benefaciens, Ferroplasma acidiphilum and other microbes. The tests performed included batch small-scale tests in 12-well Microwell plates (MWPs) with only an iron source, tests in MWPs with both an iron and sulfur source, and a semi-continuous test in 1 L bioreactors with a pyritic tailings material. In all studies, increasing concentrations of Ni2+ and Cr3+ were tested to investigate how these metals influenced microbialfacilitated iron oxidation, microbial growth, pH, redox potential and the microbial speciation of the cultures. Results show the significance of a single component in the system: for the MWP tests in the presence of no sulfur, nickel was more toxic to the microbes of both consortia, but when sulfur was present, the opposite was seen. Considering the BRGM-KCC culture, the maximum tolerated concentrations (MTCs) in the MWPs without sulfur were 4 and 7.5 g/L for nickel and chromium, respectively, and in the MWPs with sulfur, they were > 4 and < 2 g/L for nickel and chromium, respectively. Studies of the ability of the BRGM-KCC culture to tolerate increasing nickel and chromium concentrations in the semi-continuous bioreactor system in the presence of pyritic tailings confirmed that the microorganisms could tolerate nickel more readily than chromium in the presence of reduced sulfur. At 24 g/L nickel, the change in growth and oxidation was small. Conversely, at 4 g/L of chromium, most microbes were severely inhibited with cell numbers decreasing and iron oxidation ceasing. An important consideration observed in the project was the decoupling of microbial growth and iron oxidation, demonstrated previously in stress environments. In some tests, the iron oxidation achieved in the presence of chromium was higher than tests containing nickel; however, the cell numbers were significantly lower. This indicates that increased iron oxidation may occur as a stress response where microorganisms oxidise more iron to obtain more energy for cell maintenance. The implication of this is that in certain bioreactors, metals can be purposefully added (below the MTC) to increase iron oxidation without the requirement for additional CO2 supply. However, for this to be sustainable in systems requiring continuous operation, sufficient microbial growth is needed to sustain the population and this was not observed under conditions of chromium inhibition. Another important finding is related to the microorganism, Fp. acidiphilum. In almost all experiments, this microbe was able to maintain its numbers, regardless of the metal inhibitor, metal concentration and increased or decreased numbers of other microorganisms. Even in the semi-continuous bioreactor tests where all other microorganisms experienced a decrease in cell numbers at 6 g/L chromium, Fp. acidiphilum was able to maintain its numbers at around 7.16 x 107 cells/mL. Fp. acidiphilum has also been observed in commercial bioreactors, with some previously bacterial-dominated cultures seeing a shift towards the archaeon. Fp. acidiphilum is clearly a robust microbe found in many instances in laboratories and industrially, and thus understanding its behaviour and tolerance levels is becoming increasingly important. The results show the dynamic nature of bioleaching microorganisms. The work presented here contributes to knowledge on acidophilic bioleaching microorganisms so that systems can be designed where bioleaching efficiency can be maximised, and wastes can become a more utilised commodity. This work adds value by increasing the amount of information available on common bioleaching microorganisms with regards to metal tolerance.